Estudo da interação solo-estrutura e sua influência em recalques de edificações - Gusmão, Alexandre Duarte (1990)
The aim of this work is to analyse the factors that control the mechanism of soil-structure interaction in buildings and their influence on the behaviour of them. It makes use of POULOS's formulation (1975a) that considers the building as one system (superstructure plus understructure plus foundation subsoil). A parametric study was made of the main factors that influence on the soil-structure interaction, such as relative soil-structure rigidity, number of the floors of the building, effect of the first floors, presence of foundation beams, tridimensional effect of frame, building layout in plant, among others. The results are shown in the form of non-dimensional graphics, that make possible a better understanding of the influence of these several factors. The work also presents a data bank of several buildings which have been monitored to have their settlements measured. An methodology for analysis of building settlement is formulated to discuss some effects of soil-structure interaction as the redistribution of the column loads and the tendency to have more homogeneous settlements. One case history based on the POULOS's formulation (1975a) have its results shown allowing to compare predicted settlements with the measured ones. Both the theoretical and the case histories study show the important role played by the soil-structure interaction into the building design conducting safer and more economical results.